Purification And Partial Characterization Of A Bacteriocin Produced By Lactobacillus Reuteri Isolated From Human Milk - ILAYARAJA.R; RADHAMADHAVAN (International Journal of Pharma and Bio Sciences, 2011)
Bacteriocin producing Lactobacillus reuteri strain isolated from human breast milk, showed broad spectrum of antimicrobial activity against clinical pathogens. Maximum bacteriocin production was observed at 370C and pH 7. In addition of enzymes such as α-amylase, proteinase K, Lysozyme, methanol, chloroform, ethanol, acetone and benzene were strongly inhibited bacteriocin production. The bacteriocin has purified by ammonium sulphate precipitation, dialysis and Ion exchange chromatography. Biochemically it was pure protein and the molecular weight was 10kDa. The study revealed that bacteriocin producing Lactobacillus reuteri may be used as probiotic to inhibit pathogens.